Fractionation and characterization of bio-oil from microwave-assisted pyrolysis of corn stover - Yang, Changyan; Zhang, Bo; Moen, Johannes; Hennessy, Kevin; Liu, Yuhuan; Lin, Xiangyang; Wan, Yiqin; Lei, Hanwu; Chen, Paul; Ruan, Roger (International Journal of Agricultural and Biological Engineering, 2010)
Bio-oil from thermochemical conversion of biomass is a complex mixture of polar and non-polar compounds, and cannot be used directly as a combustion engine fuel due to its low heating value, high viscosity, chemical instability, and incomplete volatility. Mixed-solvent extraction was developed to fractionate bio-oils from microwave-assisted pyrolysis of corn stover to produce light oil (a mixture of light and inflammable fuel oil components from bio-oil) with low viscosity and low combustion residue, and high value chemicals. Different fractions from bio-oil were characterized using GC/MS and TG, and a major chemical (hydroxy-butanedioic acid diethyl ester) was separated. Keywords: fractionation, characterization, pyrolysis, bio-oil, corn stover DOI: 10.3965/j.issn.1934-6344.2010.03.054-061 Citation: Changyan Yang, Bo Zhang, Johannes Moen, Kevin Hennessy, Liu Yuhuan, Lin Xiangyang, et al. Fractionation and characterization of bio-oil from microwave-assisted pyrolysis of corn stover. Int J Agric & Biol Eng, 2010; 3(3): 54<span style="font-size: 9pt; line-height: 130%; font-family: